2018
DOI: 10.1039/c8cp00218e
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism and electronic spectroscopy of protonated 1- and 2-aminonaphthalene

Abstract: Experimental and theoretical investigations of the excited states of protonated 1- and 2-aminonaphthalene are presented. The electronic spectra are obtained by laser induced photofragmentation of the ions captured in a cold ion trap. Using ab initio calculations, the electronic spectra can be assigned to different tautomers which have the proton on the amino group or on the naphthalene moiety. It is shown that the tautomer distribution can be varied by changing the electrospray source conditions, favoring eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…72 Although we note that it can be somewhat subjective to assign the "vertical transition energy" from an experimental spectrum, there is little doubt that CC2 offers significant improvement on transition energy predictions in many published studies of aromatic ions. 13,73 For the CAM- For PYRI-nicH + , a strong transition is predicted around 5.15 -5.19 eV which corresponds to the S3S0 transition for all methods and this is assigned to the major peak in the m/z 84 action spectrum in Figure 4 (both A and B). The higher energy transition centred around 5.5 eV in Figure 4 is assigned to the S4S0 for the CC2 method but assigned as the S5S0 for the TD-DFT methods.…”
Section: Action Spectroscopy Compared To Calculationsmentioning
confidence: 95%
See 4 more Smart Citations
“…72 Although we note that it can be somewhat subjective to assign the "vertical transition energy" from an experimental spectrum, there is little doubt that CC2 offers significant improvement on transition energy predictions in many published studies of aromatic ions. 13,73 For the CAM- For PYRI-nicH + , a strong transition is predicted around 5.15 -5.19 eV which corresponds to the S3S0 transition for all methods and this is assigned to the major peak in the m/z 84 action spectrum in Figure 4 (both A and B). The higher energy transition centred around 5.5 eV in Figure 4 is assigned to the S4S0 for the CC2 method but assigned as the S5S0 for the TD-DFT methods.…”
Section: Action Spectroscopy Compared To Calculationsmentioning
confidence: 95%
“…28,33 It is well known that proton affinity is an oversimplified predictor for ESI generated gasphase protomer populations, and this is well evidenced by reports showing that protomer populations can vary drastically with ESI and source conditions. 3,[12][13][14][25][26] Furthermore, cases are reported that show predictions with different computational methods can scramble the order of proton affinities, thus making it tricky to confidently predict the most stable gasphase protomer. [13][14]49 Therefore, for mass spectrometry, experimental tools that detect and assign protonation isomers are vital for validation of computational methods.…”
Section: Calculationsmentioning
confidence: 99%
See 3 more Smart Citations